Wave dynamics alteration by discontinuous flexible mats of artificial seagrass can support seagrass restoration efforts - Raúl Villanueva; Maike Paul; Torsten Schlurmann (Scientific Reports, 2023)
Abstract Seagrass restoration can be promoted through the use of artificial seagrass (ASG). However, there is no guideline for ASG design, which requires a sound understanding of the inherent hydrodynamics in a submerged environment. Present know-how primarily stems from idealized ASG attached to a fixed bed. To develop accessible field deployment for restoration, anchored prototype scale ASG mats (coconut mesh) were proposed and tested under differing wave conditions. The aim of this study was then to: 1) analyze hydrodynamic interaction of ASG mats; and 2) assess the suitability of contemporary predictive hydrodynamic models. Velocity structure and wave propagation were measured around one and two ASG mats (separated by a 2-m gap). The mats reduced orbital velocities by up to 16% (2 mats), whereby the average reduction of all tested vegetated conditions was low ( $$<10%$$ < 10 % ) compared to the non-vegetated conditions. Velocities increased above the ASG, with the gap enhancing velocity (up to 11%) instead of attenuating it. Wave decay followed an exponential decrease, further enhanced by the second mat. Current models did not capture the induced hydrodynamics for the full range of wave conditions tested, with the second mat increasing uncertainties. Wave decay models generally overestimated wave attenuation (up to 30%), except for longer wave periods. Nevertheless, for the full range of conditions, the models provide accurate insight into the expected magnitude of attenuation under field conditions. It is speculated that mat flexibility affects the surrounding hydrodynamics through inherent motion, with the gap contributing to the uncertainties.